A Study On The Implementation Of Rotation Roles To Improve Students' English Skill At The Second Year Of SMP Muhammadiyah 2 Karanganyar - Rintomi N.H, Rintomi N.H (2012)
This research aims at (1) describing a study on the implementation of rotating roles to improve students english skill of the second year of SMP Muhammadiya2 Karanganyar and (2) finding the problems faced by the students and the teacher during the teaching and learning speaking skill using retelling story. In collection the data, the writer used obsecrvation, interview, and document. This research paper is about a study on the implementation of rotating roles to improve students english skill of the second year of SMP Muhammadiya2 Karanganyar. Rotating Role is a kind of method to develop the student's competence in vocabulary mastery, to comprehend the story, to develop their creativity to Improving by their own words and develop their own imagination about the story. Retelling story is independent work task. The students do the task independently, based on their own competence. The results of the research show that: 1) teaching speaking using retelling story influences the students speaking master, 2) The students are very enthusiastic in learning speaking, most of them have high motivation in joining the class and great part of the students participate to be active in front of the class. 3) Teaching speaking using retelling story is very effective.